Evaluating the development of worker cooperatives by the National Department of Public Works of South Africa. - Ariyo, Ignatius (My University, 2014)
ABSTRACT The government of South Africa has identified the development of cooperatives as a critical intervention to alleviate poverty. Different national departments are expected to promote the development of cooperatives within the activities of their mandate. The purpose of this research was to investigate the causes of the lack of success in the development of worker cooperatives by the National Department of Public Works and to make recommendations on how the challenges can be overcome. The methodology used in for this research was qualitative and involved the interviewing of twenty respondents using a structured questionnaire. Eighteen of the respondents were from worker cooperatives and two were officials from the National Department of Public Works. The key findings of this research are that the worker cooperatives being developed by the National Department of Public Works have challenges caused by poor governance, lack of access to finance, lack of access to markets, inadequate training and lack of access to a cooperative development support federation. In order to improve the development of worker cooperatives by the department, it is recommended that better training be provided to cooperatives to improve governance and management, funding be made available to cooperatives, linkages be established with other departments to market services and a cooperative development support federation be established in collaboration with the Department of Trade and Industry.
MBA 2014
Keywords: Development, Worker Cooperatives.